Sultan Hamengkubawana II and The Dutch In The Political Vortex of the Kasultanan Yogyakarta (1808-1811) - Mahardi, Nasta Ayundra Oktavian (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The reign of Sultan Hamengkubawana II in 1808-1811 was full of political turmoil from within and outside the palace. The feud with Daendels was a cold war between the Sultan who was stubborn and unwilling to submit to the Company. The Dutch wanted to create a new order for their colony with the changes they made. Yogyakarta, with Sultan Hamengkubawana II refusing, certainly received some pressure which resulted in unprecedented turmoil. This research will focus on the conflict that occurred between the Sultan and the Dutch. In addition, this research also reviews the internal conflicts that occurred in the palace. The internal conflicts that occurred in the palace also had the role of the Dutch. This research chooses the background time between 1808 and 1811. During this period, the Kasultanan Yogyakarta was in turmoil. In no less than three years, there was a colonial leadership that occupied Java and caused changes that had never happened before. Namely by the French-Dutch envoy, Herman Willem Daendels as Governor General of the Dutch East Indies. The analysis of this period is quite important considering that Yogyakarta would experience a new era of governmental order in a relatively short period of time.